Compact SIDGS Filtering Power Divider With Three-Port 10-GHz Reflectionless Range - Li, Qingxian; Tang, Hongxin; Tang, Deshan; Deng, Zhixian; Luo, Xun (IEEE transactions on circuits and systems. II, Express briefs, 2022)
In this brief, a compact high isolation filtering power divider (FPD) with wide stopband and wide-band three-port reflectionless operation is proposed. Such FPD consists of a trigonometric substrate-integrated defected ground structure (SIDGS) based resonator and three absorptive networks. The good stopband performance is achieved by using the trigonometric SIDGS. Meanwhile, the absorptive networks based on common-gate topology capable of absorbing the out-of-band reflected signals are connected to the SIDGS resonator, which provides the wideband reflectionless operation in all three ports of the FPD. To verify the mechanisms mentioned above, a FPD operated at 2.10 GHz (i.e., \boldsymbol {f_{0}} ) is fabricated, which exhibits a 42 dB stopband rejection level up to 20 GHz (i.e., 9.5\boldsymbol {f_{0}} ). The measured reflectionless range with return loss lower than −10 dB is up to 10 GHz in all three ports. The core size of the FPD is about 0.36\,\,\boldsymbol {λ _{g}} × 0.38\,\,\boldsymbol {λ _{g}} , where \boldsymbol {λ _{g}} is the microstrip guided wavelength at the center frequency.